Altered von Willebrand factor subunit proteolysis and multimer processing associated with the Cys2362Phe mutation in the B2 domain - Casonato, Alessandra; Marco, Luigi De; Gallinaro, Lisa; Sztukowska, Maryta; Mazzuccato, Mario; Battiston, Monica; Pagnan, Antonio; Ruggeri, Zaverio M. (Thrombosis and Haemostasis, 2007)
The normal von Willebrand factor (vWF) multimer pattern results from the ADAMTS-13 cleavage of the Tyr1605-Met1606 bond in the A2 domain of vWF. We identified a patient with severe von Willebrand disease (vWD) homozygously carrying a Cys to Phe mutation in position 2362 of vWF with markedly altered vWF multimers and an abnormal proteolytic pattern. The proband’s phenotype was characterized by a marked drop in plasma vWF antigen and ristocetin cofactor activity, and a less pronounced decrease in FVIII. The vWF multimers lacked any triplet structure, replaced by single bands with an atypical mobility, surrounded by a smear, and abnormally large vWF multimers. Analysis of the plasma vWF subunit's composition revealed the 225 kDa mature form and a single 205 kDa fragment, but not the 176 kDa and 140 kDa fragments resulting from cleavage by ADAMTS-13.The 205 kDa fragment was distinctly visible, along with the normal vWF cleavage products, in the patient's parents who were heterozygous for the Cys2362Phe mutation. Their vWF levels were mildly decreased and vWF multimers were organized in triplets, but also demonstrated abnormally large forms and smearing. Our findings indicate that a proper conformation of the B2 domain, which depends on critical Cys residues, may be required for the normal proteolytic processing of vWF multimers.
Keywords: von Willebrand factor; von Willebrand disease; vWF multimers; vWF proteolysis; vWF processing